1999
DOI: 10.1046/j.1365-2036.1999.00464.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of curcumin and placebo on human gall‐bladder function: an ultrasound study

Abstract: On the basis of the present findings, it appears that curcumin induces contraction of the human gall-bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 7 publications
1
42
1
2
Order By: Relevance
“…Agents that can induce the gall bladder to contract and empty itself (e.g., erythromycin, fatty meals, and amino acids) have been shown to reduce gallstone formation. In a randomized, double-blind, crossover study involving 12 healthy volunteers [178], 20 mg curcumin produced a positive cholekinetic effect that led to 29% contraction of the gall bladder. A subsequent study indicated that doses of 40 and 80 mg curcumin produced 50% and 72% contraction of the gall bladder volume, respectively.…”
Section: Curcumin May Prevent Gallstone Formationmentioning
confidence: 99%
“…Agents that can induce the gall bladder to contract and empty itself (e.g., erythromycin, fatty meals, and amino acids) have been shown to reduce gallstone formation. In a randomized, double-blind, crossover study involving 12 healthy volunteers [178], 20 mg curcumin produced a positive cholekinetic effect that led to 29% contraction of the gall bladder. A subsequent study indicated that doses of 40 and 80 mg curcumin produced 50% and 72% contraction of the gall bladder volume, respectively.…”
Section: Curcumin May Prevent Gallstone Formationmentioning
confidence: 99%
“…Previous studies showed that high concentration of curcumin causes chromosome aberrations, astrocyte cell death, teratogenic effect, embryo-, and reproductive toxicities (Ganiger and others 2007;Wu and others 2007; BurgosMorón and others 2010; Romero-Hernández and others 2013). Rasyid and Lelo (1999) found that curcumin should not recommend for gallstones patients inasmuch as it induces contraction of human gallbladder.…”
Section: Safetymentioning
confidence: 99%
“…A single oral dose of 20 mg of curcumin appeared to induce contraction of the gallbladder as adjudged by ultrasound scanning in human volunteers, compared to an amylum placebo. 55 Two potential surrogate biomarkers of the efficacy of curcumin were evaluated in the blood of patients with advanced colorectal cancer who received up to 180 mg of curcumin per day for up to 4 months. 56 In three patients on 36 mg of curcumin daily, lymphocytic activity of GST was decreased with time to reach 41% of control (untreated) on day 29 of treatment.…”
Section: Dose-effect Relationshipsmentioning
confidence: 99%